Ideological and artistic world in the novel by А. Nothomb “Métaphysique des tubes” - BELYAVSKAYA, Mariia (Accents and Paradoxes of Modern Philology, 2019)
Works by the Belgian Francophone author Amelie Nothomb (born Fabienne Claire Nothomb) (in 1966), the author of more than thirty works, honoured with the range of literary awards. Poetological analysis and studies of А. Nothomb idiostyle contributes to the research of those changes that take place in modern literature. Analyzed the peculiar genre-gender transformation that predetermines the specificity of the work and involves diffusion of features of epic and dramatic genders and genres synthesis. A communicative authorial intention, that is realized in dialogic modus of narration, topical interest of ideological-thematic layer and method of deep psycholization of images, is stressed out as well as a formation and functioning of intrigue as the author’s device of plot formation. The analysis of plot in the work testifies that the author goes back to the classical model of a plot. А. Nothomb creates to the character of a man in search of the “truth” that on plot and ideological levels forms the unity in the formation of genre matrix of the novel initiation. The individual psychological situation of personality in authorial vision becomes the reason of a plot conflict that hangs over substantial type.